Liudvikas Adomas Jucevičius, vicar of Švenčionys Parish: the Environment of the Clergyman and his Academic-Publicist Activity - Burba, Domininkas (Knygotyra, 2022)
The article is researching the life events of the Lithuanian man of letters, clergyman, ethnographer, folklorist, writer, publicist, historian and translator Liudvikas Adomas Jucevičius (Ludwik Adam Jucewicz, 1813–1846) while focusing on the years 1838–1840 when he was serving as the vicar in Švenčionys Parish. It was during these years that such famous works as literary legends as Baltijos jūros karalienė (en. The Queen of the Baltic Sea) and Džiugo kalnas (en. Džiugas Hill) were created. Simultaneously, Liudvikas Adomas Jucevičius created the works Lietuvių liaudies priežodžiai (en. Lithuanian Folk Proverbs) and Žemaitijos bruožai (en. The Features of Samogitia) which are still of high relevance to the Lithuanian academic community. The article reveals the starting point of the academic-publicist activity of this prominent personality at Vilnius Roman Catholic Spiritual academy which encouraged his academic pursuits in Švenčionys. The article also explores his deeds for the benefit of Švenčionys Parish. Finally, the academic, publicist and creative activity of Liudvikas Adomas Jucevičius during this period is researched. The focus is laid on the creative path of the personality in the context of the contemporary political and cultural developments in the society. Thereby, the emphasis of the article is not on the investigation of the content of the texts by Liudvikas Adomas Jucevičius, but rather on their spread and transfer to other publications thus highlighting the popularity of his writings at the time with the objective to trace the causes of the success of the texts.